Psychology - Myers, David G. (New York : Worth Publishers, 2007)
Presents coverage of cultural and gender diversity and research studies in such areas as neuroscience and cognition, and includes a pedagogical programme that promotes multicultural perspectives and critical thinking. This introductory "Psychology" textbook is meant for undergraduate Psychology student.
Includes glossary reference and index.
Keywords: psychology